Psychological Burnout among Medical Personnel at the Emergency Departments during COVID-19 Pandemic - تشعبت، ياسمينة (جامعة وهران2 محمد بن أحمد, 2022)
جاءت هذه الدراسة للكشف عن مستوى الاحتراق النفسي الذي يعاني منه الطاقم الطبي للاستعجالات بالمؤسسة الاستشفائية العمومية تريشين إبراهيم بغرداية دولة الجزائر، نظرا للضغوطات التي تفرضها عليهم مهنتهم وخاصة مع انتشار وباء الكورونا "COVlD19" وذلك من خلال معرفة مستوى الاحتراق النفسي عندهم. ومن أجل هذا استخدمنا المنهج الوصفي، حيث تكونت عينة الدراسة من (86) فرد من الطاقم الطبي اختيرت بطريقة عشوائية. وذلك باستخدام مقياس "ماسلاش وجاكسون" (1981) لحساب شدة الاحتراق النفسي، وقد أشارت النتائج إلى أن الطاقم الطبي للاستعجالات يعانون من مستوى متوسط من الاحتراق النفسي.
This study aimed at investigating the reality, extent, and dimensions of burnout among medical personnel at the emergency departments during COVID-19 pandemic. A descriptive analysis approach was employed on a sample consisting of 86 medical personnel working at the emergency departments of some hospitals in Ghardaia state, Algeria. Data collection was carried out by means of a localized version of "Maslach Burnout Inventory" that included three main dimensions indicating burnout (i.e. emotional exhaustion, depersonalization, and diminished sense of personal accomplishment). Results revealed that participants perceived moderate levels of emotional exhaustion (mean= 29.51, standard deviation = 11.20), moderate levels of depersonalization (mean= 20.58, standard deviation= 5.93), and high levels of diminished sense of personal accomplishment (mean= 35.41, standard deviation= 7.16). These results proved that medical personnel working at the emergency departments experience burnout during the outbreak of COVID-19 pandemic.
Keywords: المؤسسات الصحية -- الاحتراق النفسي -- فيروس كورونا (كوفيد-19) -- مصلحة الاستعجالات -- الجزائر